Photocatalytic Mineralization of Organic Acids over Visible-Light-Driven Au/BiVO4 Photocatalyst. (27th May 2013) - Pingmuang, Kanlaya; Wetchakun, Natda; Kangwansupamonkon, Wiyong; Ounnunkad, Kontad; Inceesungvorn, Burapat; Phanichphant, Sukon
Abstract : Au/BiVO4 visible-light-driven photocatalysts were synthesized by coprecipitation method in the presence of sodium dodecyl benzene sulfonate (SDBS) as a dispersant. Physical characterization of the obtained materials was carried out by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), UV-Vis diffuse reflectance spectroscopy (DRS) and Brunauer, and Emmett and Teller (BET) specific surface area measurement. Photocatalytic performances of the as-prepared Au/BiVO4 have also been evaluated via mineralizations of oxalic acid and malonic acid under visible light irradiation. XRD and SEM results indicated that Au/BiVO4 photocatalysts were of almost spherical particles with scheelite-monoclinic phase. Photocatalytic results showed that all Au/BiVO4 samples exhibited higher oxalic acid mineralization rate than that of pure BiVO4, probably due to a decrease of BiVO4 band gap energy and the presence of surface plasmon absorption upon loading BiVO4 with Au as evidenced from UV-Vis DRS results. The nominal Au loading amount of 0.25 mol% provided the highest pseudo-first-order rate constant of 0.0487 min −1 and 0.0082 min −1 for degradations of oxalic acid (C2 ) and malonic acid (C3 ), respectively. By considering structures of the two acids, lower pseudo-first-order rate constantly obtained in the case of malonic acid degradation was likely due to an increased complexity of the degradation mechanism of the longer chain acid.